2021
DOI: 10.31269/triplec.v19i2.1264
|View full text |Cite
|
Sign up to set email alerts
|

Counter-Hegemonic Decision Premises in Commons-Based Peer Production: A Degrowth Case Study

Abstract: Capitalism is evidently the main cause of ecological degradation, climate change and social inequality. Degrowth as a counter-hegemony opposes the capitalist imperatives of economic growth and capital accumulation and radically seeks to transform society towards sustainability. This has strong political economic implications. Economic organisations and modes of production are essential in overcoming capitalist hegemony. This article investigates two commons-based peer production (CBPP) organisations in a quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In an empirical study, Robra et al (2020) found that if peer production is commons-based, it is a part of degrowth if organizations are explicitly oriented toward eco-sufficiency. A year later, Robra et al (2021) added that "a strong awareness of the contradiction of CBPP [Commons-Based Peer-Production] in the capitalist system and the aim to shift societal structures helps to survive this contradiction and align with degrowth counter-hegemony simultaneously" (p. 363). Commons are social relations, practices, and work based on established regulations, which require community.…”
Section: Conclusion: Degrowth As a Social-ecological Transformations ...mentioning
confidence: 99%
“…In an empirical study, Robra et al (2020) found that if peer production is commons-based, it is a part of degrowth if organizations are explicitly oriented toward eco-sufficiency. A year later, Robra et al (2021) added that "a strong awareness of the contradiction of CBPP [Commons-Based Peer-Production] in the capitalist system and the aim to shift societal structures helps to survive this contradiction and align with degrowth counter-hegemony simultaneously" (p. 363). Commons are social relations, practices, and work based on established regulations, which require community.…”
Section: Conclusion: Degrowth As a Social-ecological Transformations ...mentioning
confidence: 99%
“…Roulet & Bothello, 2020), although the vast majority of degrowth scholars are critical of this view (e.g. Hinton, 2021;Robra et al, 2021). In this regard, it is argued that whilst there is certainly a role for entrepreneurship in a degrowth society, the latter should look radically different from conventional business models in the for-profit sector.…”
Section: Towards a Degrowth Agenda For Sustainability Marketingmentioning
confidence: 99%